The Study of Natural Law in The Philosophy of Law on Legal Thought in Indonesia - Wahdah, Azzhara Nikita; Triadi, Irwan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study explores the relevance and contribution of natural law theory to the development of a just legal system in Indonesia, particularly in the context of human rights protection. Employing a normative juridical approach and literature review spanning classical to contemporary legal philosophy, the article examines natural law principles as a universal and enduring moral foundation. The findings reveal that both irrational natural law—rooted in divine values—and rational natural law—derived from human reason—hold significant potential to reinforce the legitimacy of Indonesia’s positive law. While structural and cultural challenges hinder the integration of natural law into the national legal framework, opportunities arise through the enhancement of justice-oriented regulations, recognition of customary law, and the adoption of restorative justice principles. The study advocates for harmonizing positive law with natural law values as a strategic pathway toward inclusive legal reform centered on human dignity.